Podocyte Infolding Glomerulopathy, First Case Report From North America. (October 2021) - Ting, Julie Anne; Hung, Wayne; McRae, Susanna A.; Barbour, Sean J.; Copland, Michael; Riazy, Maziar
Rationale: Podocyte infolding glomerulopathy (PIG) is a newly described condition with only 37 cases reported worldwide. Due to its rarity, the pathogenesis and evolution of this disease is unclear. This case report contributes to our collective knowledge about the clinical and histological progression of this disease. Presenting concerns of the patient: Over the course of a year, a 52-year-old Malaysian woman with no known prior medical history developed progressively worsening edema and other findings consistent with nephrotic syndrome. Diagnosis: Unlike most patients with PIG, this patient did not have any autoimmune disease. She was Hepatitis B core antibody positive with a Hepatitis B surface antibody >1000, suggesting prior Hepatitis B infection with immunity. A renal biopsy was performed which was consistent with PIG. A second renal biopsy was done 2 years later which again showed characteristic findings of PIG with worsened podocyte effacement but no interval change in chronicity. Interventions: The patient was treated with blood pressure control and renin-angiotensin-aldosterone system (RAAS) blockade with irbesartan and spironolactone. She was also treated with prednisone at 1 mg/kg for 2 months followed by a taper for a total of 7 months of prednisone treatment. Outcomes: The patient had a partial response to a course of prednisone. However, since stopping steroids, her proteinuria and renal function has been gradually worsening. Teaching points: PIG is mostly found in patients of East Asian descent. It presents as proteinuria and is often associated with autoimmune disease but can be idiopathic. It is characterized on renal biopsy by infolding or protrusion of podocyte cytoplasm into glomerular basement membrane, as well as intramembranous cytoplasmic microspherules or microtubules. Atypical membranous nephropathy should be ruled out prior to diagnosis. Unlike membranous nephropathy, PIG usually responds at least partially to steroid monotherapy. To our knowledge, this is the first reported case of PIG from North America. Furthermore, it is the first case of PIG with repeat biopsy showing interval worsening of PIG rather than either resolution of PIG or transformation of PIG to a different diagnosis.